The luster of lost things - Keller, Sophie Chen, 1988- (G.P. Putnam's Sons, 2017)
"A boy with an uncanny ability to find lost objects must embark on his most important search yet in order to save his mother's enchanted dessert shop, the only place he's ever called home. There's only one place in the world that lonely twelve-year-old Walter Lavender Jr. feels at home: The Lavenders, his mother's unusual West Village dessert shop ... When the mysterious and magical Book at the heart of the shop vanishes and a landlord threatens closure, it's up to Walter to find the Book and save the shop. Despite--or because of--a communication disorder that renders him speechless and friendless, Walter has a special ability to find lost things. In fact, the only thing he's failed to find is his father, a pilot lost in a presumed plane crash at sea before Walter was born. Accompanied by Milton, his best friend and overweight golden retriever, Walter's quest will take him around and under New York City, into subway tunnels and soaring over Central Park, from bottle collecting in Chinatown to racing through the Met, and introduce him to the extraordinary and forgotten people of this fantastical city. Along the way he will discover his voice and learn what it means to truly be found"--